Preparation method of composite nanofiltration membrane, prepared composite nanofiltration membrane and application thereof, and solvent separation and recovery method

By combining the polyamide separation layer containing aromatic sulfone group on the polyimide support layer, the composite nanofiltration membrane was prepared, which solved the problems of low separation stability and low solvent purity in the existing nanofiltration membrane, and achieved efficient recycling of lubricant dewaxed solvents and good solvent resistance.

CN119607923AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311169390.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing nanofiltration membranes have low separation stability during use, low purity of recovered solvents, and the separation stability of the membrane in ketobenzene solvent is unknown.

Method used

By combining the polyamide separation layer containing aromatic sulfone group on the polyimide support layer, a composite nanofiltration membrane is prepared by chemical crosslinking and interfacial polymerization to improve its solvent resistance and service life.

Benefits of technology

The composite nanofiltration membrane has basically maintained stable recovery performance of lubricant dewaxed solvents within 500 hours, and has good solvent resistance, which can effectively improve the membrane's retention performance and flux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607923A_ABST
    Figure CN119607923A_ABST
Patent Text Reader

Abstract

The invention relates to the field of chemical engineering, and discloses a preparation method of a composite nanofiltration membrane, the prepared composite nanofiltration membrane and application thereof, and a solvent separation and recovery method, the preparation method of the composite nanofiltration membrane comprises the following steps: (1) carrying out chemical cross-linking reaction on a polyimide membrane and a cross-linking modified solution to obtain a polyimide supporting layer; and (2) contacting the polyimide supporting layer with a hydrocarbon solution of an acyl chloride mixture, and carrying out interfacial polymerization reaction to obtain the composite nanofiltration membrane containing the polyimide supporting layer and a polyamide separation layer containing arylsulfonyl, wherein the crosslinking modification solution is an alcohol solution of a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer. According to the preparation method, the solvent resistance of the composite nanofiltration membrane can be greatly improved, and the service life of the composite nanofiltration membrane is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical industry, and in particular to a method for preparing a composite nanofiltration membrane, the prepared composite nanofiltration membrane and application thereof, and a method for separating and recovering a solvent. Background Art

[0002] Solvent dewaxing technology is one of the most commonly used technologies in lubricant production. The dewaxing solvent used is mainly a mixture of toluene and butanone. At present, the solvent in the ketone-benzene dewaxing and deoiling unit in industry is generally recovered by evaporation-stripping method. Due to the large amount of solvent used, solvent recovery is the most energy-consuming unit in the entire process. Solvent-resistant nanofiltration technology is a membrane separation technology that can be used for organic solvent recovery. Solvent-resistant nanofiltration technology can selectively pass solvents with small molecular weight and intercept high-value-added products or impurities with large molecular weight in pressure-driven mode. Since the separation process does not involve phase change, solvent recovery can be achieved at low energy consumption.

[0003] Regarding solvent recovery during lubricating oil dewaxing, US005429748A discloses a polyimide nanofiltration membrane for the recovery of ketone-benzene dewaxing solvents, with a membrane flux of 7.6 GSFD at -10°C and 600 psi pressure, and a lubricating oil retention rate of 96%. However, the nanofiltration membrane has membrane contamination problems during use and needs to be cleaned regularly.

[0004] CN109694745B, CN109692572B and CN109694746B disclose a series of methods for recovering lubricating oil raw material dewaxing solvent using P84 polyimide nanofiltration membrane. The average content of organic solvent in the membrane permeate obtained by the recovery method is high, and the effect of recovering dewaxing solvent at room temperature is good. The modified P84 nanofiltration membrane (CN101678286A) produced by Evonik of Germany is used in the methods. After the P84 membrane is prepared by the phase inversion method, it needs to be immersed in a diamine solution for 24 hours for chemical cross-linking. The membrane preparation time is long, and the long-term separation stability of the membrane is not tested. The separation stability of the membrane in ketone benzene solvent is unknown.

[0005] CN100363094C discloses a method for preparing a polyimide nanofiltration membrane, which comprises first preparing a polyamic acid nanofiltration membrane and then subjecting it to amidation treatment. The polyimide prepared by the method is used for the recovery of the ketone-benzene dewaxing solvent of lubricating oil, but the interception rate of the lubricating oil is only about 90%, and the purity of the recovered solvent is low.

[0006] CN103464012B discloses a method for preparing an organic solvent-resistant polyimide nanofiltration membrane using an inorganic salt porogen. The method controls the number of finger-like pores in the membrane and the thickness of the dense separation layer by adding an inorganic salt to the polyimide casting solution. The polyimide prepared by the method is used to recover the ketone-benzene dewaxing solvent of lubricating oil. Although the interception rate of lubricating oil can reach 90%, there is a lack of solvent recovery rate data.

[0007] CN107174971A discloses a method for preparing a solvent-resistant polyamide nanofiltration membrane. The method uses a porous carrier such as a cross-linked polyimide or a cross-linked polybenzimidazole as a support layer, and a polyamide layer is compounded thereon to prepare a membrane. In the invention, an aqueous solution of polyamine and m-phenylenediamine are subjected to an interfacial polymerization reaction with a monoacyl chloride or polyacyl chloride or a mixture thereof to prepare a polyamide layer. The separation membrane does not mention the long-term tolerance of the membrane to solvents.

[0008] Therefore, there is a need for a nanofiltration membrane that can tolerate solvents for a long time while ensuring good separation properties. Summary of the invention

[0009] The purpose of the present invention is to overcome the problems of low separation stability and low purity of recovered solvent of nanofiltration membranes used in membrane separation technology in the prior art, and to provide a method for preparing a composite nanofiltration membrane, a prepared composite nanofiltration membrane and its application, and a method for solvent separation and recovery. The preparation method can greatly improve the solvent resistance of the composite nanofiltration membrane and extend the service life of the composite nanofiltration membrane by compositely forming a separation layer of polyamide containing aromatic sulfone groups on a polyimide support layer. Within 500 hours of operation, the recovery performance of the composite nanofiltration membrane for lubricating oil dewaxing solvent remains basically stable.

[0010] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a composite nanofiltration membrane, wherein the method comprises the following steps: (1) chemically cross-linking the polyimide membrane with a cross-linking modification solution to obtain a polyimide support layer; (2) contacting the polyimide support layer with a hydrocarbon solution of an acyl chloride mixture to perform an interfacial polymerization reaction to obtain a composite nanofiltration membrane comprising a polyimide support layer and a polyamide separation layer containing an aromatic sulfone group; The cross-linking modification solution is an alcohol solution of a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer.

[0011] The second aspect of the present invention provides a composite nanofiltration membrane prepared by the preparation method described in the first aspect, wherein the composite nanofiltration membrane comprises a polyimide support layer and a polyamide separation layer containing aromatic sulfone groups.

[0012] The third aspect of the present invention provides an application of the composite nanofiltration membrane described in the second aspect in the field of separation and recovery of organic solvents.

[0013] The fourth aspect of the present invention provides a method for solvent separation and recovery, wherein the method comprises: using the composite nanofiltration membrane described in the second aspect to separate the lubricating oil dewaxing solvent, wherein the separation conditions include: a separation temperature of 10-30°C and an operating pressure of 2-4MPa.

[0014] Through the above technical solution, the beneficial effects obtained are as follows: (1) The preparation method provided by the present invention is simple. The prepared composite nanofiltration membrane is a composite separation layer of polyamide containing aromatic sulfone groups on a polyimide support layer. The polyamide and the polyimide are cross-linked by covalent action, which can greatly improve the solvent resistance and lubricating oil retention performance of the nanofiltration membrane. After 500 hours of use, the solvent recovery performance can still be maintained stably. (2) In the present invention, preferably, the preparation of the composite nanofiltration membrane can flexibly adjust the retention performance and flux of the composite nanofiltration membrane by changing the type of solvent used in the post-reaction treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is an infrared spectrum of the composite nanofiltration membrane prepared in Example 1; Figure 2 These are a scanning electron microscope cross-sectional view of the composite nanofiltration membrane prepared in Example 1 and a partially enlarged scanning electron microscope cross-sectional view of the polyamide separation layer, a is a scanning electron microscope cross-sectional view of the composite nanofiltration membrane, and b is a partially enlarged scanning electron microscope cross-sectional view of the polyamide separation layer. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] A first aspect of the present invention provides a method for preparing a composite nanofiltration membrane, wherein the method comprises the following steps: (1) chemically cross-linking the polyimide membrane with a cross-linking modification solution to obtain a polyimide support layer; (2) contacting the polyimide support layer with a hydrocarbon solution of an acyl chloride mixture to perform an interfacial polymerization reaction to obtain a composite nanofiltration membrane comprising a polyimide support layer and a polyamide separation layer containing an aromatic sulfone group; The cross-linking modification solution is an alcohol solution of a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer.

[0018] In the present invention, the preparation method provided is to chemically crosslink and modify the imide group of the polyimide membrane with the diamine monomer, and further contact the modified product with an acyl chloride mixture to perform an interfacial polymerization reaction, thereby obtaining a composite nanofiltration membrane comprising a polyimide support layer and a polyamide separation layer containing an aromatic sulfone group. The solvent resistance of the composite nanofiltration membrane can be greatly improved, and the service life of the composite nanofiltration membrane can be extended. Within 500 hours of operation, the recovery performance of the composite nanofiltration membrane for the lubricating oil dewaxing solvent remains basically stable.

[0019] According to the present invention, preferably, in step (1), the polyimide film is prepared by the following method: The polyimide powder is mixed with a solvent, and the mixed solution is degassed to obtain a polyimide film casting solution, which is then coated on a polypropylene non-woven fabric and scraped into a film, and the film is immersed in water and an alcohol reagent to obtain a polyimide film.

[0020] In the present invention, the degassing method of the mixed solution is not particularly limited, and a conventional degassing method in the art can be used. Preferably, the degassing is static degassing and / or ultrasonic degassing, and the degassing time is not particularly limited. According to a preferred embodiment of the present invention, a static degassing method is adopted, and the static degassing includes: at room temperature, the mixed solution is allowed to stand for 12-24 hours.

[0021] In the present invention, the method of mixing the polyimide powder and the solvent is not particularly limited, as long as the polyimide powder is fully dissolved. Preferably, the mixing is carried out by stirring, with a stirring rate of 500-1200 rpm / min and a stirring time of 1-20 h.

[0022] In the present invention, the polyimide powder can be purchased from a commercial source or prepared by an existing method, and those skilled in the art can select the appropriate method. In the present invention, preferably, the polyimide powder is dried in a vacuum before use at a drying temperature of 60-100°C.

[0023] In the present invention, the film scraping device is not particularly limited. According to a preferred embodiment of the present invention, the film scraping can be carried out in a film scraping machine. The film scraping speed is not particularly limited, preferably 20-200 mm / s, and the film scraping thickness is not particularly limited, preferably 150-300 µm, preferably 150-250 µm. According to a preferred embodiment of the present invention, after the film scraping is completed, the film scraping product is quickly placed in deionized water for 1-3 hours, and then transferred to an alcohol reagent and soaked for more than 12 hours to obtain a polyimide film.

[0024] According to the present invention, preferably, the mass concentration of polyimide in the polyimide casting solution is 15-25wt%, preferably 16-22wt%.

[0025] According to the present invention, preferably, the solvent is a mixed solvent of N,N-dimethylformamide and 1,4-dioxane.

[0026] According to the present invention, preferably, the mass ratio of N,N-dimethylformamide to 1,4-dioxane in the solvent is 0.3-5:1, preferably 2-4:1. In the present invention, preferably, the polyimide mixed solution casting solution is prepared by using the above solvent combination, and the pore size distribution of the obtained polyimide membrane is more uniform, and the uniformity of the obtained composite nanofiltration membrane is better.

[0027] According to the present invention, preferably, the alcohol reagent is selected from at least one of methanol, ethanol and isopropanol.

[0028] According to the present invention, preferably, in the cross-linked modified solution, the total mass concentration of the sulfonyl diphenylamine monomer and the short-chain aliphatic diamine monomer is 0.5-8wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, or any range therebetween, preferably 1-5wt%.

[0029] In the present invention, preferably, the cross-linking modification solution further includes an active auxiliary agent. The active auxiliary agent can improve the activity of the subsequent interfacial polymerization reaction of the sulfonyl-containing diphenylamine monomer and the sulfonyl chloride monomer. Preferably, the active auxiliary agent is selected from at least one of triethylamine, potassium hydroxide, sodium hydroxide and sodium bicarbonate. The mass concentration of the active auxiliary agent in the cross-linking modification solution is 0.1-1wt%, preferably 0.1-0.5wt%.

[0030] According to the present invention, preferably, the mass ratio of the sulfonyl-containing diphenylamine monomer to the short-chain aliphatic diamine monomer is 1-3:1, preferably 1-2:1.

[0031] According to the present invention, preferably, the solvent contained in the cross-linking modification solution is selected from at least one of methanol, ethanol and isopropanol. In the present invention, preferably, the solvent contained in the cross-linking modification solution is consistent with the alcohol reagent for preparing the polyimide film, which can control the swelling state of the polyimide film to be the same as that during modification, so as to better cause the cross-linking reaction.

[0032] According to the present invention, preferably, in step (1), the volume of the cross-linking modification solution added per square meter of the polyimide membrane is 1-10 L, preferably 2-5 L.

[0033] According to the present invention, preferably, the conditions of the chemical cross-linking reaction include: a reaction temperature of 10-35° C., preferably 15-25° C.; and a reaction time of 5-30 min, preferably 10-30 min.

[0034] In the present invention, the polyimide film will swell in an alcohol solvent, and some sulfonyl-containing diphenylamine monomers and short-chain aliphatic diamine monomers can enter the polyimide, and chemical crosslinking connects the diamine to the imine group on the polyimide through a covalent bond, and the crosslinking is mainly performed on the surface of the polyimide film. The short-chain aliphatic diamine monomer, due to its linear structure and low molecular weight, can more easily enter the interior of the polyimide film, crosslink with the polyimide segment, and improve the solvent resistance of the film.

[0035] In the present invention, polyimide is chemically cross-linked with a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer, and the imide ring of the polyimide is opened, wherein the C=O bond is connected to the NH of the sulfonyl-containing diphenylamine monomer or the short-chain aliphatic diamine monomer to form an amide group. S=O groups and CH groups are introduced on the surface of the polyimide film by chemical cross-linking, which can prove the occurrence of cross-linking of the polyimide with the sulfonyl-containing diphenylamine monomer and the short-chain aliphatic diamine monomer.

[0036] In the present invention, by infrared spectroscopy ( Figure 1 ) and X-ray photoelectron spectroscopy (Table 1) were used to characterize the polyimide film before and after diamine modification. The infrared spectrum showed that after diamine modification, the 1711 cm -1 and 1780cm -1 The C=O stretching vibration peak of the imide group at 1360 cm -1 The CN stretching vibration peak intensity of the imide group at 1540-1560cm -1 The CN / NH peaks of the amide group and 1620-1640 cm -1 The C=O peak intensity of the amide group at 3300 cm -1 The stretching vibration peak of NH after diamine grafting was newly added at 1310-1360cm -1 and 1135-1165cm -1 A new characteristic peak of S=O after cross-linking of diphenylamine monomer containing sulfonyl group was added at 3100-3200cm -1 A new CH stretching vibration peak on the unsaturated carbon after cross-linking of the sulfonyl-containing diphenylamine monomer was added, indicating that the sulfonyl-containing diphenylamine monomer and polyimide were cross-linked; 2700-3000 cm -1The CH stretching vibration peak on the saturated carbon at 100 nm shifted significantly and increased in intensity, indicating that the short-chain aliphatic diamine monomers and polyimide were cross-linked, and new saturated CH bonds were introduced on the membrane surface. The characterization results of X-ray photoelectron spectroscopy showed that after diamine modification, S elements appeared on the membrane surface, the C element content on the membrane surface decreased significantly, and the N and O element contents increased significantly, which corresponded to the above infrared spectroscopy characterization results, indicating that the diamine monomers and polyimide membranes were cross-linked.

[0037] According to the present invention, preferably, the sulfonyl diphenylamine monomer is 4,4'-sulfonyl diphenylamine and / or 3,3'-sulfonyl diphenylamine. In the present invention, the diphenylamine monomer is limited to the above-mentioned sulfonyl diphenylamine monomer. Cross-linking on the polyimide can introduce aromatic sulfone groups on the polymer chain segment to improve the solvent resistance of the membrane.

[0038] According to the present invention, preferably, the short-chain aliphatic diamine monomer is selected from at least one of ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine and 1,6-hexanediamine, preferably ethylenediamine and / or 1,3-propylenediamine. In the present invention, if the molecular chain of the short-chain aliphatic diamine monomer is too long, the aliphatic diamine monomer is difficult to diffuse into the interior of the polyimide film when the cross-linking time is short, and the cross-linking effect is poor.

[0039] According to the present invention, preferably, the acid chloride mixture comprises terephthaloyl chloride and aromatic sulfonyl chloride compounds. In the present invention, the terephthaloyl chloride and aromatic sulfonyl chloride compounds in the acid chloride mixture react with the imine groups generated by the cross-linking reaction on the polyimide membrane and the remaining unreacted diamine monomers to form a dense polyamide separation layer containing aromatic sulfone groups.

[0040] In the present invention, by infrared spectroscopy ( Figure 1 ) and X-ray photoelectron spectroscopy (Table 1) were used to characterize the composite nanofiltration membrane prepared by interfacial polymerization reaction with the addition of the acyl chloride mixture. The characterization results of infrared spectroscopy showed that after the interfacial polymerization reaction with the addition of the acyl chloride mixture, the 3300cm -1 The NH stretching vibration peaks at 1540-1560cm -1 The CN / NH peak intensity weakened at 950-1000cm -1 An SN stretching vibration peak appeared at the interface. The characterization results of X-ray photoelectron spectroscopy showed that after the interfacial polymerization reaction, the contents of C and N elements on the membrane surface decreased, while the contents of O and S elements increased. The above results indicate that the imine groups generated after the cross-linking reaction on the polyimide membrane and the remaining unreacted diamine monomer and acyl chloride mixture underwent interfacial polymerization reaction to form a dense polyamide separation layer containing aromatic sulfone groups.

[0041] According to the present invention, preferably, in step (2), the volume of the acyl chloride mixture solution added per square meter of the polyimide support layer is 2-6 L, preferably 2.5-4 L.

[0042] According to the present invention, preferably, in the hydrocarbon solution of the acyl chloride mixture, the total mass concentration of the acyl chloride mixture is 0.05-2wt%, preferably 0.1-1wt%. In the present invention, the total mass concentration of the acyl chloride mixture is limited, and the rate of the interfacial polymerization reaction and the density of the generated interfacial polymerization layer can be controlled. The concentration of the acyl chloride mixture is too low, the interfacial polymerization reaction efficiency is low, the generated polyamide layer is not dense enough, and the interception effect is not good; the concentration of the acyl chloride mixture is too high, and the interfacial polymerization reaction is too violent, which may cause the polyamide layer to be too thick, and the thickness is uneven, resulting in low membrane flux, and no significant improvement in interception performance.

[0043] According to the present invention, preferably, the conditions of the interfacial polymerization reaction include: a reaction temperature of 10-35°C, preferably 15-25°C; a reaction time of 0.5-5 min, preferably 1-5 min. In the present invention, the interfacial polymerization reaction is fast and the reaction temperature is low, which can avoid side reactions at high temperatures, and there is no special limitation on the reaction equipment.

[0044] According to the present invention, preferably, the aromatic sulfonyl chloride compound is 1,3-benzenedisulfonyl chloride and / or biphenyl-4,4-disulfonyl chloride. In the present invention, the aromatic sulfonyl chloride compound is used to carry out interfacial polymerization reaction with a diamine monomer, so as to introduce a sulfonamide group into the polyamide separation layer, thereby further enhancing the solvent resistance of the membrane.

[0045] According to the present invention, preferably, in the acid chloride mixture, the mass ratio of terephthaloyl chloride to aromatic sulfonyl chloride is 0.1-2:1, preferably 0.3-1.5:1. In the present invention, adding terephthaloyl chloride and aromatic sulfonyl chloride to participate in the interfacial polymerization reaction simultaneously can improve the efficiency of the interfacial polymerization reaction, form a denser polyamide separation layer containing aromatic sulfone groups, and improve the membrane's retention performance and solvent resistance to lubricating oil.

[0046] According to the present invention, preferably, the hydrocarbon solution of the acyl chloride mixture contains a solvent selected from at least one of n-pentane, n-hexane, n-heptane, n-octane, toluene and trimethylbenzene.

[0047] According to the present invention, preferably, in step (2), after the interfacial polymerization reaction is completed, a termination reaction treatment is further performed, wherein the termination reaction treatment process comprises: soaking the polymerization product obtained by the interfacial polymerization reaction at the interface with an organic solvent for 0.5 min-1 min, and then curing at 60-100°C for 2-10 min.

[0048] According to the present invention, preferably, the organic solvent is selected from at least one of n-hexane, isopropanol and formamide, preferably n-hexane. In the present invention, an organic solvent is used for termination reaction treatment, and the organic solvent reacts with the unreacted acyl chloride monomer remaining in the interfacial polymerization reaction to perform end-capping, and the amount of the organic solvent is not particularly limited. The use of the organic solvent of the above preferred embodiment for termination reaction treatment is helpful for regulating the retention performance and membrane flux of the composite nanofiltration membrane. After the interfacial polymerization reaction is completed, an organic solvent is used to terminate the reaction, and while removing the acyl chloride monomer remaining in the interfacial polymerization reaction, no carboxyl group is introduced.

[0049] The second aspect of the present invention provides a composite nanofiltration membrane obtained by the preparation method described in the first aspect, wherein the composite nanofiltration membrane comprises a polyimide support layer and a polyamide separation layer containing aromatic sulfone groups.

[0050] In the present invention, the polyamide separation layer containing aromatic sulfone groups is obtained by interfacial polymerization of a mixture of sulfonyl-containing diphenylamine monomers and short-chain aliphatic diamine monomers and acyl chlorides, wherein the aromatic sulfone groups in the polyamide segments are connected to sulfonamide groups or amide groups.

[0051] According to the present invention, preferably, the thickness of the polyimide support layer is 150-300µm, preferably 150-250µm. In the present invention, the polyimide support layer comprises a cross-linked modified polyimide film and a polypropylene non-woven fabric layer.

[0052] According to the present invention, preferably, the thickness of the polyamide separation layer containing aromatic sulfone groups is 100-400 nm, preferably 150-300 nm. In the present invention, if the thickness of the polyamide separation layer containing aromatic sulfone groups is too large, the membrane flux of the composite nanofiltration membrane is low; if the thickness is too small, the membrane separation effect is poor.

[0053] In the present invention, the polyamide containing aromatic sulfone groups has a structure as shown in formula (I) or formula (II): Formula (I);

[0054] Formula (II);

[0055] Among them, R is C or S=O group (S is connected to N), and R1 is H or a polyimide polymer chain segment.

[0056] In the present invention, R1 is introduced by cross-linking the diamine monomer with the polyimide. When the aforementioned sulfonyl-containing diphenylamine monomer and the aforementioned short-chain aliphatic diamine monomer are not completely cross-linked with the polyimide polymer segment, R1 is the remaining H from the reaction of the uncross-linked diamine monomer with the acyl chloride monomer. According to a preferred embodiment of the present invention, the polyimide is a commercial product of BASF with the brand name Matrimid 5218, with a weight average molecular weight of 30,000-40,000 Da. The polyimide polymer segment obtained by the aforementioned chemical cross-linking of the short-chain diamine monomer with the polyimide has a structure shown in formula (III), Formula (III).

[0057] In the present invention, R is introduced by the added terephthaloyl chloride and aromatic sulfonyl chloride compounds, and when the sulfonyl diphenylamine monomer reacts with the terephthaloyl chloride, R is a C atom; when the sulfonyl diphenylamine monomer reacts with the aromatic sulfonyl chloride compounds, R is an S=O group. The aromatic sulfone group-containing polyamide separation layer is obtained by polycondensing the sulfonyl diphenylamine monomer with the acyl chloride monomer to remove H and Cl atoms respectively.

[0058] In the present invention, the short-chain aliphatic diamine monomer can also undergo a condensation reaction with terephthaloyl chloride and aromatic sulfonyl chloride compounds to remove H and Cl atoms respectively, so that the two acyl chloride monomers in the aromatic sulfone group-containing polyamide separation layer can also be connected to the residues of the short-chain aliphatic diamine monomer after removing two H atoms.

[0059] The third aspect of the present invention provides an application of the composite nanofiltration membrane described in the second aspect in the field of separation and recovery of organic solvents.

[0060] According to the present invention, preferably, the composite nanofiltration membrane is used for separation and recovery of butanone and toluene solvents in lubricating oil dewaxing solvents. In the present invention, the composite nanofiltration membrane has good recovery performance for lubricating oil dewaxing solvents, high retention rate for lubricating oil base oils, and good solvent resistance.

[0061] The fourth aspect of the present invention provides a method for solvent separation and recovery, wherein the method comprises: using the composite nanofiltration membrane described in the second aspect to separate the lubricating oil dewaxing solvent, wherein the separation conditions include: a separation temperature of 10-30°C and an operating pressure of 2-4MPa.

[0062] In the present invention, the equipment for separation and recovery of the solvent is not particularly limited, and those skilled in the art can select conventional separation equipment. In the present invention, preferably, a small cross-flow membrane separation device is used to verify the separation and recovery of the lubricating oil dewaxing solvent by the composite nanofiltration membrane. In the present invention, the feed flow rate of the lubricating oil dewaxing solvent is 10-60 mL / min.

[0063] In the present invention, under the condition of operating pressure of 4 MPa, separation temperature of 25°C and membrane permeability of 40%, the retention rate of the composite nanofiltration membrane for lubricating oil base oil in ketone benzene solvent is maintained between 93% and 99%, and the membrane flux is between 15 and 30 kg / m 2 After 500 hours of long-term solvent immersion, the recovery performance of the composite nanofiltration membrane for lubricating oil dewaxing solvent remained basically stable, with good solvent resistance, and can meet the requirements of long-term use in organic solvents.

[0064] In the present invention, the raw materials of the lubricating oil dewaxing solvent include butanone, toluene and lubricating oil base oil, and the mass percentage of each component is not particularly limited. Preferably, the raw material composition of the lubricating oil dewaxing solvent includes 20-60wt% butanone, 20-60wt% toluene and 10-30wt% lubricating oil base oil.

[0065] According to a particularly preferred embodiment of the present invention, a method for preparing a composite nanofiltration membrane is characterized in that the method comprises the following steps: (1) chemically cross-linking the polyimide membrane with a cross-linking modification solution to obtain a polyimide support layer; (2) contacting the polyimide support layer with a hydrocarbon solution of an acyl chloride mixture to perform an interfacial polymerization reaction to obtain a composite nanofiltration membrane comprising a polyimide support layer and a polyamide separation layer containing an aromatic sulfone group; Wherein, the cross-linking modification solution is an alcohol solution of a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer; In the cross-linking modification solution, the total mass concentration of the sulfonyl-containing diphenylamine monomer and the short-chain aliphatic diamine monomer is 1-5wt%; The mass ratio of the sulfonyl-containing diphenylamine monomer to the short-chain aliphatic diamine monomer is 1-2:1; In the hydrocarbon solution of the acyl chloride mixture, the total mass concentration of the acyl chloride mixture is 0.1-1wt%; The acyl chloride mixture includes terephthaloyl chloride and aromatic sulfonyl chloride compounds; In the acyl chloride mixture, the mass ratio of terephthaloyl chloride to aromatic sulfonyl chloride compounds is 0.3-1.5:1.

[0066] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, normal temperature refers to 25°C; The thickness of the polyimide support layer was measured by a screw micrometer, and the thickness of the polyamide separation layer containing aromatic sulfone groups was measured by scanning electron microscopy cross-sectional images; The surface element composition changes and functional group composition changes of the polyimide membrane, the cross-linked polyimide support layer and the composite nanofiltration membrane were measured by X-ray photoelectron spectroscopy and infrared spectroscopy. The polyimide raw material was a commercial product of BASF with the brand name Matrimid 5218. The polyimide powders used were vacuum dried at 80°C for 1 h before being dissolved.

[0067] Example 1 (1-1) Prepare 10 g of a mixed solvent of N,N-dimethylformamide (DMF) and 1,4-dioxane in a mass ratio of 3:1, add 1.8 g of polyimide powder thereto, stir and blend at 800 rpm / min for 6 h to fully dissolve the polyimide, and then let the solution stand for degassing for more than 12 h.

[0068] (1-2) The film scraping machine was set to a film thickness of 250 µm and a speed of 100 mm / s, and then the degassed polyimide casting solution was poured onto the polypropylene non-woven fabric to start film scraping. After the film scraping was completed, it was quickly placed in deionized water for 3 h, and then transferred to an alcohol reagent and soaked for 12 h to obtain a polyimide film.

[0069] (1-3) Cross-linking modification solution: prepare 1 wt% 1,3-propylenediamine and 1 wt% 4,4'-diaminodiphenyl sulfone with ethanol as the solvent, and add 0.2 wt% triethylamine to the solution; Prepare a solution of an acyl chloride mixture: prepare terephthaloyl chloride with a mass concentration of 0.05wt% and 1,3-benzenedisulfonyl chloride with a mass concentration of 0.1wt%, and use n-hexane as the solvent.

[0070] (1-4) At room temperature, place 80cm 2 The polyimide membrane was immersed in 25 mL of cross-linking modification solution for 20 min, then taken out, and the residual solution on the membrane was blown off to obtain a polyimide support layer; (2) Pour 25 mL of a solution of an acyl chloride mixture on the surface of the polyimide support layer, allow the interfacial polymerization reaction to proceed for 5 minutes at room temperature, and then quickly remove the solution; then pour n-hexane reagent on the membrane surface, soak for 1 minute, remove the n-hexane, and place in air for curing at 80°C for 5 minutes to obtain a composite nanofiltration membrane.

[0071] Figure 2 The SEM cross-sectional view of the composite nanofiltration membrane prepared in Example 1 and the partially enlarged SEM cross-sectional view of the polyamide separation layer, wherein Figure a is the SEM cross-sectional view of the composite nanofiltration membrane, and Figure b is the partially enlarged SEM cross-sectional view of the polyamide separation layer. The thickness of the polyimide support layer in the composite nanofiltration membrane is 240 μm. Figure 2It can be observed that the thickness of the separation layer of the polyamide containing aromatic sulfone groups is 225 nm.

[0072] Table 1 shows the elemental composition (X-ray photoelectron spectroscopy) of the surface of polyimide membrane, diamine-modified polyimide membrane and composite nanofiltration membrane.

[0073] Table 1

[0074] Example 2 The method of Example 1 was followed, except that in step (1-3), the concentration of 1,3-propylenediamine was 1.2 wt % and the concentration of 4,4'-sulfonyldiphenylamine was 0.8 wt %. A composite nanofiltration membrane was obtained.

[0075] Example 3 The method of Example 1 is followed, except that in step (1-3), 1,3-propylenediamine is replaced with 1,4-butylenediamine of equal mass to obtain a composite nanofiltration membrane.

[0076] Example 4 The method of Example 1 was followed, except that the solution of the acyl chloride mixture in step (1-3) was changed to 0.15 wt % terephthaloyl chloride and 0.05 wt % 1,3-benzenedisulfonyl chloride, with n-hexane as the solvent, to obtain a composite nanofiltration membrane.

[0077] Example 5 (1-1) Prepare 10 g of a mixed solvent of N,N-dimethylformamide (DMF) and 1,4-dioxane in a mass ratio of 2:1, add 1.8 g of polyimide powder thereto, stir and blend at 800 rpm / min for 6 h to fully dissolve the polyimide, and then let the solution stand for degassing for more than 12 h.

[0078] (1-2) The film scraping machine was set to a film thickness of 300 µm and a speed of 100 mm / s, and then the degassed polyimide casting solution was poured onto the polypropylene non-woven fabric to start film scraping. After the film scraping was completed, it was quickly placed in deionized water for 3 h, and then transferred to an alcohol reagent and soaked for 12 h to obtain a polyimide film.

[0079] (1-3) Cross-linking modification solution: prepare 0.8 wt% of 1,6-hexanediamine and 1.2 wt% of 3,3'-sulfonyl diphenylamine, with ethanol as the solvent; Prepare a solution of an acyl chloride mixture: prepare terephthaloyl chloride with a mass concentration of 0.05wt% and 1,3-benzenedisulfonyl chloride with a mass concentration of 0.1wt%, and use n-hexane as the solvent.

[0080] (1-4) At room temperature, place 80 cm2 The polyimide membrane was immersed in 25 mL of cross-linking modification solution for 20 min, then taken out and the residual solution on the membrane was blown off to obtain a polyimide support layer; (2) Pour 25 mL of a solution of an acyl chloride mixture on the surface of the polyimide support layer, allow the interfacial polymerization reaction to proceed for 5 minutes at room temperature, and then quickly remove the solution; then pour n-hexane reagent on the membrane surface, soak for 1 minute, remove the n-hexane, and place in air for curing at 80°C for 5 minutes to obtain a composite nanofiltration membrane.

[0081] Example 6 The method of Example 1 was followed, except that the 1,3-benzenedisulfonyl chloride in step (2) was replaced with an equal mass of trimesoyl chloride to obtain a composite nanofiltration membrane.

[0082] Example 7 The method of Example 1 was followed, except that the diamine modification time in step (1-4) was changed to 2 min, and the interfacial polymerization reaction time in step (2) was changed to 1 min. A composite nanofiltration membrane was obtained.

[0083] Comparative Example 1 The method of Example 1 is followed, except that in step (1-3), the cross-linking modification solution contains only 2 wt % of 4,4'-sulfonyl diphenylamine to obtain a composite nanofiltration membrane.

[0084] Comparative Example 2 The method of Example 1 is followed, except that in step (1-3), the cross-linking modification solution contains only 2 wt% of 1,3-propylenediamine to obtain a composite nanofiltration membrane.

[0085] Comparative Example 3 The polyimide support layer was prepared by the same steps (1-1) to (1-4) as in Example 1, and the polyimide support layer was directly used for recovering the lubricating oil dewaxing solvent without performing the subsequent steps.

[0086] Test Example 1 In the present invention, the separation performance of the prepared solvent-resistant composite nanofiltration membrane is evaluated using a small cross-flow membrane separation device built in the laboratory. The raw material composition of the lubricating oil dewaxing solvent is 40wt% butanone + 40wt% toluene + 20wt% lubricating oil base oil. The effective area of ​​the composite nanofiltration membrane used for the test is 12.56cm 2 The raw material amount of lubricating oil dewaxing solvent is 60 g, the separation temperature is 20°C, the operating pressure is 4 MPa, and the feed flow rate of lubricating oil dewaxing raw material solvent is 60 mL / min. The results are shown in Table 2.

[0087] (1) The flux of the composite nanofiltration membrane to treat the lubricating oil base oil dewaxing solvent is calculated by the following formula: J = Q / (A t), where J is the membrane flux (kg / m 2 / h), Q is the amount of permeate collected (kg), A is the effective membrane area of ​​the composite nanofiltration membrane (m 2 ), t is time (h); (2) The retention rate of the composite nanofiltration membrane for lubricating oil base oil is calculated by the following formula: R = (C Y -C P ) / C Y ×100%, where R is the retention rate of lubricating oil base oil (%), C Y is the mass fraction of lubricating oil base oil in the raw material, C P is the mass fraction of lubricating base oil in the permeate; (3) The membrane permeability of the composite nanofiltration membrane in the process of treating lubricating oil base oil is calculated by the following formula: X = M P / M Y ×100%, where X is the film permeability (%), M Y is the mass of raw materials, M P is the mass of the collected permeate. The test results in Table 2 show that the membrane permeation rate is 40%; Table 2

[0088] It can be seen from the results in Table 2 that the composite nanofiltration membrane of the embodiment of the present invention has a higher membrane flux and a retention rate for lubricating oil base oil, can still maintain a relatively high retention rate after 500 hours, and has good solvent resistance.

[0089] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite nanofiltration membrane, characterized in that: The method comprises the following steps: (1) chemically cross-linking the polyimide membrane with a cross-linking modification solution to obtain a polyimide support layer; (2) contacting the polyimide support layer with a hydrocarbon solution of an acyl chloride mixture to perform an interfacial polymerization reaction to obtain a composite nanofiltration membrane comprising a polyimide support layer and a polyamide separation layer containing an aromatic sulfone group; The cross-linking modification solution is an alcohol solution of a sulfonyl-containing diphenylamine monomer and a short-chain aliphatic diamine monomer.

2. The preparation method according to claim 1, wherein In step (1), the polyimide film is prepared by the following method: The polyimide powder is mixed with a solvent, the mixed solution is degassed to obtain a polyimide film casting solution, the polyimide film casting solution is coated on a polypropylene non-woven fabric, and a film is scraped, and the film is immersed in water and an alcohol reagent to obtain a polyimide film; Preferably, the mass concentration of polyimide in the polyimide casting solution is 15-25wt%, preferably 16-22wt%; Preferably, the solvent is a mixed solvent of N,N-dimethylformamide and 1,4-dioxane; Preferably, the mass ratio of N,N-dimethylformamide to 1,4-dioxane in the solvent is 0.3-5:1, preferably 2-4:1; Preferably, the alcohol reagent is selected from at least one of methanol, ethanol and isopropanol.

3. The preparation method according to claim 1 or 2, wherein In the cross-linking modification solution, the total mass concentration of the sulfonyl-containing diphenylamine monomer and the short-chain aliphatic diamine monomer is 0.5-8wt%, preferably 1-5wt%; Preferably, the mass ratio of the sulfonyl-containing diphenylamine monomer to the short-chain aliphatic diamine monomer is 1-3:1, preferably 1-2:1; Preferably, the cross-linking modification solution contains a solvent selected from at least one of methanol, ethanol and isopropanol; Preferably, the conditions of the chemical cross-linking reaction include: a reaction temperature of 10-35° C., preferably 15-25° C.; and a reaction time of 5-30 min, preferably 10-30 min.

4. The preparation method according to claim 3, wherein The sulfonyl-containing diphenylamine monomer is 4,4'-sulfonyl diphenylamine and / or 3,3'-sulfonyl diphenylamine; Preferably, the short-chain aliphatic diamine monomer is at least one selected from ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine and 1,6-hexanediamine.

5. The preparation method according to any one of claims 1 to 4, wherein: The acyl chloride mixture includes terephthaloyl chloride and aromatic sulfonyl chloride compounds; Preferably, in the hydrocarbon solution of the acyl chloride mixture, the total mass concentration of the acyl chloride mixture is 0.05-2wt%, preferably 0.1-1wt%; Preferably, the conditions for the interfacial polymerization reaction include: a reaction temperature of 10-35° C., preferably 15-25° C.; and a reaction time of 0.5-5 min, preferably 1-5 min.

6. The preparation method according to claim 5, wherein: The aromatic sulfonyl chloride compound is 1,3-benzenedisulfonyl chloride and / or biphenyl-4,4-disulfonyl chloride; Preferably, in the acyl chloride mixture, the mass ratio of terephthaloyl chloride to aromatic sulfonyl chloride is 0.1-2:1, preferably 0.3-1.5:1; Preferably, the hydrocarbon solution of the acyl chloride mixture contains a solvent selected from at least one of n-pentane, n-hexane, n-heptane, n-octane, toluene and trimethylbenzene.

7. The preparation method according to any one of claims 1 to 6, wherein: In step (2), after the interfacial polymerization reaction is completed, a termination reaction treatment is further performed, wherein the termination reaction treatment process comprises: soaking the polymerization product obtained by the interfacial polymerization reaction at the interface with an organic solvent for 0.5 min-1 min, and then curing at 60-100° C. for 2-10 min; Preferably, the organic solvent is selected from at least one of n-hexane, isopropanol and formamide, preferably n-hexane.

8. A composite nanofiltration membrane obtained by the preparation method according to any one of claims 1 to 7, wherein: The composite nanofiltration membrane comprises a polyimide support layer and a polyamide separation layer containing aromatic sulfone groups; Preferably, the thickness of the polyimide support layer is 150-300 µm, preferably 150-250 µm; Preferably, the thickness of the polyamide separation layer containing aromatic sulfone groups is 100-400 nm, preferably 150-300 nm.

9. Application of the composite nanofiltration membrane according to claim 8 in the field of separation and recovery of organic solvents; Preferably, the composite nanofiltration membrane is used for separation and recovery of butanone and toluene solvents in lubricating oil dewaxing solvents.

10. A method for separating and recovering a solvent, characterized in that: The method comprises: using the composite nanofiltration membrane of claim 8 to separate the lubricating oil dewaxing solvent, wherein the separation conditions include: a separation temperature of 10-30° C. and an operating pressure of 2-4 MPa.

Citation Information

Patent Citations

  • Preparation method of polyimide nanometer filtering membrane

    CN100363094C

  • Cross-linked polyimide membranes

    CN101678286A

  • Novel method for preparing organic-solvent-resisting polyimide nanofiltration membrane through inorganic salt pore-forming agent

    CN103464012B

  • Solvent resistant polyamide nanofiltration membranes

    CN107174971A

  • Methods for recovering solvents from dewaxing light lubricating oil feedstocks and methods for dewaxing light lubricating oil feedstocks.

    CN109692572B